The Bahamas : 2019 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2019)
Growth has returned after years of stagnation. The reform-oriented government is tackling structural issues, with notable achievements in the fiscal area. The financial sector is sound and resilient to current stability threats, but credit remains scarce. The offshore sector faces heightened international scrutiny and the government is taking steps to strengthen compliance with AML/CFT and tax transparency standards. Tourism and related foreign investments will support growth in the near-term, while low competitiveness and diversification dampen medium-term prospects. Growth would suffer from a slowdown in the U.S. or higher oil prices, and hurricane vulnerability persists. Reform momentum could stall, undermining fiscal consolidation efforts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet